Republic of Mozambique: Final Report General and Provincial Assembly Elections - European Union Election Observation Missionn (European Union Election Observation Mission, 2019)
On 15 October, Mozambicans elected the president, members of the Assembly of the Republic, members of the 10 provincial assemblies, and 10 provincial governors. Although there was a considerable number of participants, including recently registered political parties, the electoral process was dominated by the three main parties: the ruling Mozambican Liberation Front (FRELIMO), the main opposition Mozambican National Resistance (RENAMO), and the Mozambican Democratic Movement (MDM)
Keywords: G - Mozambique / Moçambique; L - english / inglês; electoral geography / geografia eleitoral